IMPROVING ENGLISH VOCABULARY THROUGH SEMANTIC MAPPING STRATEGY AMONG GRADE 8 SMP NEGERI 12 PEMATANG SIANTAR - Cindy Yani Simorangkir; Dumaris E Silalahi; Sara Stedani Malau; Sry Tama Butar Butar (JR-ELT (Journal of Research in English Language Teaching), 2025)
Mastery of vocabulary plays a vital role in language acquisition, as it enables learners to comprehend, express idea, and construct meaning effectively. Nevertheless, many students still encounter challenges in retaining and using new vocabulary due to a lack of contextualized learning activities and repetitive teaching practices. This research aimed to examine the effectiveness of the Semantic Mapping Strategy (SMS) in enhancing English Vocabulary avhievement among eight-grade students at SMP Negeri 12 Pematang Siantar. A Quantitative approach was adopted  throught a pre-experimental one-group pre-test and post-test and post test. The analysis shoed a remarkable improvement in students' vocabulary scores, with the mean rising from 52.4 in the pre test to 89.5 in the post-test. Furthermore, the number of outcomes demonstrate that the Semantic Mapping Strategy effectively promotes meaningful be concluded that SMS can be regarded as an efficient and engaging method to improve vocabulary master inEFL classrooms.